PENGUATAN LITERASI BAHASA ARAB MELALUI PENDAMPINGAN KETERAMPILAN IMLĀ' BAGI SANTRI PEMULA DI MA NW MATARAM - Wira Purwata; Suparlan; Munawirsazali; Zubaidi (LPPM STAI Muhammadiyah Probolinggo, 2026)
The low level of imlā’ (Arabic dictation) skills remains one of the major obstacles in strengthening Arabic literacy among beginner students in Islamic schools. This condition was also identified among beginner students at MA NW Mataram, who experienced difficulties in writing Arabic letters correctly, connecting letters, applying vowel marks, and composing Arabic words and sentences according to orthographic rules. This community engagement program aimed to improve students' imlā’ skills, strengthen basic Arabic literacy, and enhance learning motivation through structured mentoring activities. The program employed the Participatory Learning and Action (PLA) approach, consisting of preliminary observation, needs assessment, module development, pre-test, mentoring through short lectures, demonstrations, repetitive drills, peer tutoring, direct practice, and post-test evaluation. The results indicated a significant improvement in participants' imlā’ skills, with the average score increasing from 60.5 in the pre-test to 84.3 in the post-test, representing a 39.3% improvement. In addition, participants demonstrated higher learning motivation, greater classroom participation, and improved Arabic writing competence. Teachers and school administrators also expressed positive responses toward the program. Therefore, the mentoring model proved effective in strengthening Arabic literacy through improving imlā’ skills and has the potential to be implemented sustainably in other Islamic educational institutions.